Breastfeeding Practices and Determinant Factors of Exclusive Breastfeeding among Mothers of Children Aged 0–23 Months in Northwestern Romania - Anamaria Cozma-Petruţ (MDPI AG, 2021)
In terms of breastfeeding (BF) practices in Romania, there is a lack of up-to-date data. The aim of the present study was to assess current BF practices, and to investigate the factors associated with exclusive BF (EBF) under 6 months of age in northwestern Romania. A structured questionnaire was used to collect data among 1399 mothers of children aged 0–23 months, recruited between March and June 2019, from the community. BF practices were evaluated based on the World Health Organization indicators for assessing infant and young child feeding practices, whereas determinants of EBF were explored using logistic regression models. Almost all mothers (95.7%) breastfed their child at least once. The EBF rate was 46.7%, the continued BF rate at one year of age was 54.2%, and the continued BF rate at 2 years of age was 30.3%. The place of delivery and parental leave duration were strong determinants of EBF. The improving rates observed in this study for all the BF practices assessed suggest the continuation of efforts to develop effective national policies and programs for promoting, protecting, and supporting BF in Romania. Particular emphasis should be given to the creation in maternity hospitals of an environment that is supportive towards breastfeeding.